2017
DOI: 10.7566/jpsj.86.073703
|View full text |Cite
|
Sign up to set email alerts
|

Plain s-Wave Superconductivity near Magnetic Criticality: Enhancement of Attractive Electron–Boson Coupling Vertex Corrections

Abstract: Recent experiments revealed that the plain s-wave state without any sign-reversal emerges in various metals near magnetic criticality. To understand this counter-intuitive phenomenon, we study the gap equation for the multiorbital Hubbard-Holstein model, by analyzing the vertex correction (VC) due to the higher-order electron-correlation effects. We find that the phonon-mediated orbital fluctuations are magnified by the VC for the susceptibility (χ-VC). In addition, the charge-channel attractive interaction is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
(36 reference statements)
1
18
0
Order By: Relevance
“…This is qualitatively similar to d-electron systems without SOI as shown in Fig.2(c) in Ref. [35]. In conclusion, U -VC in f -electron systems give significant contribution as well as in d-electron systems.…”
Section: Important Roles Of U -Vcsupporting
confidence: 86%
See 2 more Smart Citations
“…This is qualitatively similar to d-electron systems without SOI as shown in Fig.2(c) in Ref. [35]. In conclusion, U -VC in f -electron systems give significant contribution as well as in d-electron systems.…”
Section: Important Roles Of U -Vcsupporting
confidence: 86%
“…We revealed that s-wave superconductivity is strongly enhanced near the magnetic criticality in multi-orbital heavy fermion systems, once moderate phonon-induced multipole fluctuations exist as shown in Fig.6. Note that the depairing effect of Coulomb interaction is reduced by the multiorbital screening effect [35]. The present mechanism may be responsible for the fully gapped s-wave superconducting state realized in CeCu 2 Si 2 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In HF systems, phonon-mediated superconductivity can be stabilized by the AL-process for the electron-boson coupling. This mechanism may be responsible for the fully gapped s-wave state in CeCu 2 Si 2 [26,37]. These findings indicate that the AL-VC plays essential roles in HF systems…”
mentioning
confidence: 71%
“…The s þþ -wave state inferred in this study is generally a manifestation of on-site attractive interactions, but how this can overcome the strong Coulomb repulsion in such a strongly correlated electron system calls for new theoretical approaches beyond the widespread spin-fluctuation-based unconventional mechanism of superconductivity. Very recent calculations show that in the vicinity of magnetic quantum critical point, the orbital fluctuations may lead to s þþ -wave superconductivity [32]. Indeed, the importance of orbital degrees of freedom has been pointed out in several aspects for some Ce-based materials including CeM 2 Si 2 , where M is a transition metal element [33][34][35].…”
mentioning
confidence: 99%